Speaking of collaboration, friendship and the future of Italian film studies: An interview with Millicent Marcus - Marcus, Millicent and Lerner, Giovanna Faleschini and Marini-Maio, Nicoletta and Past, Elena (Journal of Italian Cinema & Media Studies, 2019)
In this written interview, Millicent Marcus responds to the editors’ questions about her trajectory as a scholar and teacher. After a brief preface, in which she inventively describes the written interview as a genre per se, Marcus’s answers to our questions contextualize her view of contemporary Italian film, her scholarly background, and her ethical approach to cinema. In this work of self-reflection, she untangles the central elements of her vision: adaptation, feminism, intersections between research and teaching and collaboration in the academy.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qaWNtcy43LjIuMTkxXzc